Squanto, friend of the white men. - Bulla, Clyde Robert; Burchard, Peter (New York, Crowell, 1954)
A biography of the Indian who went to London with some of the first English explorers, was sold into slavery in Spain, and finally returned to America where he befriended the Pilgrims when they landed.
Keywords: Squanto -- Fiction; Squanto